Dari Dominasi Menuju Responsibilitas: Mazmur 8 dan Amanat Ilahi bagi Tanggung Jawab Ekologis Manusia - Leo Mardany Ruindungan (Sekolah Tinggi Teologi Injili Indonesia Yogyakarta, 2026)
The contemporary ecological crisis is often linked to the anthropocentric paradigm. The Bible is frequently challenged because certain interpretations of human authority are seen as legitimizing environmental exploitation. The primary issue lies not within the scriptural text itself, but rather within the problematic interpretation of it. Originally, the text of Psalm 8 contains no exploitative language; instead, it emphasizes humanity's absolute dependence on God. This qualitative, library-based research presents an ecotheological reading of Psalm 8:6–9. Employing morphological-syntactic analysis of the Hebrew text—encompassing verbal subjects, objects of action, verbal stems, and syntactic relations—as its primary method, this study uses the Earth Perspective framework as a reflective lens. The analytical focus is applied to the verbal stems of three main verbs in Psalm 8:6–7: watteḥassĕrēhû (Piel stem), watteʿaṭṭĕrēhû (Piel stem), and tamšîlēhû (Hiphil stem). Analysis of the pronominal object suffixes on these verbs consistently displays God as the active subject, while humans appear merely as recipients of divine action. This grammatical structure establishes the theological foundation that human dignity and authority over creation (verses 8–9) are gifts and delegated mandates rather than autonomous rights. Consequently, the human relationship with creation must shift from domination to ecological responsibility.